Paraphrasing impact on narrative unity in Disney’s theme songs - Hanif, Imaduddin; Rahima, Aulia Sahda; Rizky, Mohammad Riyadh; ’Aini, Nurhabibah Qurrotul; Azzahra, Nandhini Fardya; Al Rasid, Muhammad Shechida Alan; Caesary, Nurshafa Regina; Fadillah, Shalha Meysa Nur (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
Walt Disney is a distinguished company who has spread its well-known works of children’s series to various countries. In the process of distributing the series to numerous countries, indeed there is a translation process that must be done first. In this study, into Indonesian. The researchers limited only the paraphrasing translation method used and the effect of this method on the series’ theme songs’ narrative unity. In this article, the researchers tried to convey the translating way in the series to make it acceptable by the audience and its main goal to maintain the storyline contained in the lyrics. The theories by Dinda Gorlée and John Christman delves into the subject of the impact of paraphrasing techniques and narrative unity in the theme song translation of Disney’s children animated series. The researchers emphasized the importance of translating the theme song correctly to ensure that children can understand and enjoy the series. . This study is descriptive and qualitative in design and the results of the analysis showed that the pattern of paraphrasing techniques used in translating the theme song had significant impacts on the narrative unity of the series.